Effects on Local Temperature and Energy of Oasis City Expansion in Arid Area of Northwest China. (1st February 2020) - Zhang, Miao; Luo, Geping; Cai, Peng; Hamdi, Rafiq
Abstract : The land surface model SURFEX 7.3 was used to study climate effect of urban expansion located in oasis in arid area of Northwest China by surface and 2 m urban heat island (UHI) intensity and available energy ratio (B ). We performed a true regional development scenario and three assumed scenario simulations in 1978, 1993, 2004, and 2014, respectively. The results show that 2 m UHI always displays positive twin peaks during whole day, while surface UHI only displays a positive single peak with several hours during daytime at four seasons in the four years. Moreover, 2 m UHI intensity during night is higher than that during daytime, indicating that UHI intensity is contributed more by "trap effect" from urban complex geometry or anthropogenic heat and that surface UHI according to land surface temperature cannot reflect UHI comprehensively. The oasis-urban development resulted in local warming and increasing of B, and compared with the original undeveloped environment, local climate in the study area was in a relatively balanced state in 1978 and 1993 due to the "heating effect" of urban area and the "cooling effect" of oasis, but the offsetting effect from oasis would become weaker after1993.